Crystal structure of N,N′,N′′-tris(2-pyridinyl)phosphoric triamide, (NC5H4NH)3PO - Gholivand K.; Alavi M. D.; Pourayoubi M. (Zeitschrift für Kristallographie - New Crystal Structures, 2004)
C15H15N6OP, monoclinic, P121/n1 (no. 14), a = 10.558(2) Å, b = 13.448(2) Å, c = 21.814(4) Å, β = 92.314(4)°, V = 3094.6 Å3, Z = 8, Rgt(F) = 0.051, wRref(F2) = 0.101, T = 120 K.